Infinite-horizon mechanism design: The independent-shock approach - Alessandro Pavan; Ilya Segal; Juuso Toikka (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
These notes examine the problem of how to extend envelope theorems to infinite-horizon dynamic mechanism design settings, with an application to the design of bandit auctions.
Keywords: 330